Ingri and Edgar Parin D'Aulaire's book of Greek myths. - D'Aulaire, Ingri, 1904-; D'Aulaire, Edgar Parin, 1898- (New York : Bantam Doubleday Dell Pub., 1962)
Illustrated retellings of the myths about the gods and goddesses of ancient Greece.
"A Doubleday Book for Young Readers."
"A Yearling special."
Includes index.
Elem. School Library Collection, June 2000
Library Journal
Kirkus Review
Keywords: Classical mythology